New insights into the management of homozygous familial hypercholesterolemia patients treated with lomitapide: a single-center experience - Iannuzzo, Gabriella; Calcaterra, Ilenia Lorenza; Gentile, Marco; Stanzione, Claudia; de Ruberto, Francesca; di Taranto, Maria Donata; Cardiero, Giovanna; Fortunato, Giuliana; Minno, Matteo Di (Frontiers in Endocrinology, 2024)
Familial hypercholesterolemia (FH) is a genetic disease, usually with onset during childhood, characterized by elevated blood LDL cholesterol levels and potentially associated with severe cardiovascular complications. Concerning mutated genes in FH, such as LDLR, a small subset of FH patients presents a homozygous genotype, resulting in homozygous FH (HoFH) disease with a generally aggressive phenotype. Besides statins, ezetimibe and PCSK9 inhibitors, lomitapide (an anti-ApoB therapy) was also approved in 2012–2013 as an adjunctive treatment for HoFH. Despite its clinical efficacy, lomitapide administration should be done with caution because of the possible occurrence of side effects, such as hepatosteatosis, increased blood transaminase levels and gastrointestinal symptoms, as well as the possible deleterious interactions with other drugs. In this context, we decided to report the main available evidence on the management and monitoring of HoFH patients treated with lomitapide and to accompany this literature review with a description of our clinical experience with a subset of six HoFH patients. In conclusion, this paper aims to address an important topic for HoFH-related clinical practice that, to our knowledge, is not yet formally regulated by proper national and/or international guidelines.